Edukasi Interaktif : Literasi Digital dan Etika Bermedia Sosial bagi Peserta Didik Baru SMK Xaverius Palembang - Klaudius Jevanda BS; Latius Hermawan; Wawan Nurmansyah; Hendrik Fery Herdiatmoko; Fransiska Ninda Permata Nugraha (Lembaga Pengembangan Kinerja Dosen, 2026)
In today’s world, social media has become an everyday necessity for interacting and socializing with others, but it has both positive and negative effects, particularly on the younger generation. The roles of parents and educators are crucial in building the digital resilience of the younger generation. The solution is to provide early education to the younger generation, particularly new students for the 2025/2026 school year, during the School Orientation Program conducted by the UKMC Community Service Team. The purpose of this activity is to educate new students at SMK Xaverius Palembang to improve their understanding of digital literacy and online etiquette and to use social media more responsibly. The PkM Team served as guest speakers, presenting material on digital literacy and social media ethics, as well as real-life case studies, on Thursday, July 17, 2025, in the auditorium of SMK Xaverius Palembang. This activity is a community service initiative that uses interactive educational methods, in which the team presents five questions related to online gambling, fake news, cyberbullying, explicit content, and ending human trafficking in the form of digital posters, and the students explain them. The team also provided real-life examples and explained their causes and effects. Based on the results of the program, students demonstrated increased awareness of the risks associated with online gambling, fake news, cyberbullying, and explicit content, as well as the importance of combating human trafficking, and were more likely to adopt positive social media etiquette.